Inhibition of mitochondria ATP synthase suppresses prostate cancer growth through reduced insulin‐like growth factor‐1 secretion by prostate stromal cells. Issue 12 (19th March 2020) - Ohishi, Tomokazu; Abe, Hikaru; Sakashita, Chiharu; Saqib, Uzma; Baig, Mirza S.; Ohba, Shun‐ichi; Inoue, Hiroyuki; Watanabe, Takumi; Shibasaki, Masakatsu; Kawada, Manabu
Abstract : Modulation of prostate stromal cells (PrSCs) within tumor tissues is gaining attention for the treatment of solid tumors. Using our original in vitro coculture system, we previously reported that leucinostatin (LCS)‐A, a peptide mycotoxin, inhibited prostate cancer DU‐145 cell growth through reduction of insulin‐like growth factor 1 (IGF‐I) expression in PrSCs. To further obtain additional bioactive compounds from LCS‐A, we designed and synthesized a series of LCS‐A derivatives as compounds that target PrSCs. Among the synthesized LCS‐A derivatives, LCS‐7 reduced IGF‐I expression in PrSCs with lower toxicity to PrSCs and mice than LCS‐A. As LCS‐A has been suggested to interact with mitochondrial adenosine triphosphate (ATP) synthase, a docking study was performed to elucidate the mechanism of reduced IGF‐I expression in the PrSCs. As expected, LCS‐A and LCS‐7 directly interacted with mitochondrial ATP synthase, and like LCS‐A and LCS‐7, other mitochondrial ATP synthase inhibitors also reduced the expression of IGF‐I by PrSCs. Furthermore, LCS‐A and LCS‐7 significantly decreased the growth of mouse xenograft tumors. Based on these data, we propose that the mitochondrial ATP synthases–IGF‐I axis of PrSCs plays a critical role on cancer cell growth and inhibition could be a potential anticancer target for prostate cancer. Abstract : What's new? The secretion by prostate stromal cells (PrSCs) of insulin‐like growth factor‐1 (IGF‐I) fuels prostate cancer (PC) cell proliferation. IGF‐I expression by PC cells can be reduced by leucinostatin‐A (LCS‐A), a fungal nanopeptide. Here, the authors investigated a panel of synthetic LCS‐A compounds and identified a derivative, LCS‐7, that specifically reduces IGF‐I expression in PrSCs. Docking analyses show that LCS‐7 interacts directly with mitochondrial ATP synthase to reduce IGF‐I expression. In a mouse xenograft model, LCS‐7 significantly inhibited prostate tumor growth. The findings open the path to mitochondrial ATP synthase–IGF‐I axis targeting as a novel therapeutic strategy against prostate cancer.